(untitled) (American International Journal of Sciences and Engineering Research, 2019)
Our literature includes information and explanation for indicators in chemical reactions and principle of its using which represented by (types of indicators ,pH of indicators , instrumental precipitation,…) , principles of precipitation by indicator , methods of precipitation by indicator ,types of indicators for precipitation, conditions of precipitation .